Persistent Dimer of Nanographdiyne Functionalized With Ester - Chen, Jing; Hu, Guilin; He, Jingyi; Wu, Xingzhong; Li, Yongjun (Chemistry, an Asian journal, 2025)
Controlling the self-assembly and aggregation behavior of nanographdiyne (NanoGDY) in solution is crucial for understanding the intrinsic structure-property relationships of graphdiyne. However, capturing the persistent NanoGDY dimer aggregate presents a significant challenge. Herein, we have successfully synthesized a novel ester-functionalized NanoGDY with solubilized alkyl chains at the periphery named NanoGDY-CO and investigated its aggregation behavior at different temperatures as well as different solvents by H NMR, UV-vis, and FL spectroscopy. The combination of intermolecular hydrogen bonding formed by the ester groups and π─π stacking facilitates the self-assembly of NanoGDY-CO into a persistent coplanar and slip-stacked dimer. In contrast, the branched 2-octyldodecyl substituent acts as a steric control agent preventing further aggregation of the self-assembled NanoGDY dimer. This work offers new insights into understanding and manipulating the self-assembly behavior of NanoGDYs in solution.